Determining the Sustainable Future of NGOs, From Historical and Contemporary Lenses - OdorigeCathérine Enorédia (Dunakavics, 2023)
Players in the social sector are unique partners in the global drive for a sustainable future. There however exists a precarity in the nature of this sector’s perception and incorporation which would usually leave rhetorical questions about its future. In a market economy profit making is the primary source of growth of the enterprise and its sustainability. Nonprofits do not run on objectives of profit-making, rather they address social challenges and imbalances via their value-creating activities, which ensures their potential to attract funding from corporate, governmental and private donors and volunteer support to sustain their activities. Social enterprise a business concept that blends profit with public good is proposed as a sustainable model for social service provision. Via historical and empirical evidence and nonrepresentative semi-structured interviews of NGO representatives in Hungary this research access organization’s awareness of the concept and the possibility to make a transition. Findings reveal that the obstacle to an equilibrium shift is due to the value NGOs bring to check the failings of the market economy.